3D velocity and temperature distribution measurement and characteristic analysis of swirling combustion. (April 2022) - Su, Yi; Zhang, Bin; Chen, Yifeng; Sui, Chunjie; Chen, Wei
Highlights: Theories and methods of simultaneous measurement for velocity and temperature were established. A hybrid experimental measurement system was constructed. PIV and deflection tomography were combined to diagnose complex combustion. Three-dimensional temperature and velocity fields were quantitatively reconstructed. Combustion characteristics were analysed under different structural parameters of swirl burner. Abstract: The latest research directions of combustion flow field visualisation and combustion diagnosis have been extended to the development of non-contact, multi-parameter measurement methods for qualitative analysis and multi-dimensional visualisation. Velocity and temperature are important parameters that reflect the characteristics of the combustion flow field and affect the combustion dynamics and combustion mechanism, which have become the keys to characterising and diagnosing the combustion process. Three-dimensional (3D) velocity and temperature fields of combustion were reconstructed in combination with particle image velocimetry (PIV) and deflection tomography temperature measurement methods, and swirl combustion characteristics were studied. A non-premixed burner was designed to generate a swirling flame, and an experimental system was constructed for the simultaneous measurement of velocity and temperature to acquire tracer particles and Moiré fringe images. A 3D particle recognition technology and cross-correlation algorithm were used to reconstruct a 3D combustion velocity field. The fringe displacement analytical technique and deflection angle correction iterative tomography algorithm were used to reconstruct a 3D temperature field. The effects of different swirl numbers and swirl vane positions on the characteristics of the swirl flame shape, velocity distribution, and temperature distribution were investigated. The combustion reaction and field process evolution were explained. Certain characteristics, including heat and mass transfer and flow field transport of swirling combustion, were analysed. The measurement errors were discussed.